Assessment of Skills in Inquiry Based Biology Education - Slepáková, Ivana; Kimáková, Katarína (Scientia in educatione, 2015)
International project FP7 ESTABLISH was focused on the development of methodological materials for wider use of inquiry based education (IBSE – Inquiry Based Science Education). Eleven partners participated in the creation and implementation of these materials in teaching. In Slovakia, the pilot project involved 40 teachers of biology, chemistry and physics at lower and higher secondary schools. It transpired that the teachers felt loss of control over teaching IBSE because they did not know how to identify and assess the development of pupils’ inquiry skills. There is a lack of appropriate instruments, which could help teachers in this process. The preparation of assessment tools of inquiry skills in IBSE is done within project SAILS FP7. Teachers who trial IBSE in practice participate in preparatory training focused on assessment. The creation of methods in SAILS project is based on their practical experience. The paper presents a concrete example of the assessment tool created on the basis of case studies of science teaching practise. Case studies of SAILS project contribute to shaping a more general procedure of formative and also summative assessment of pupils’ inquiry. The first step is the selection of a particular skill the teacher wants to assess and also the definition of the essential foundation, which is further developed, consolidated and expanded. The teacher provides continuous feedback to the pupil in a dialogue about how his/her skills develop and what he/she should work on. The basis for summative assessment of the pupil represents the highest level of the skills he/she achieved during the assessment period.